Сходство и различие антропоморфной пластики Южной Туркмении и Месопотамии в эпоху энеолита - Антонова, E. В. (1977)
Antonova, E. V., Parallels and Variety of Anthropomorphic Plastics of Southern Turkmenia and Mesopotamia in the Aeneolithic Age; Parallelen zu Hassuna, Halaf, Obeid.